Moving average stratification algorithm for strata boundary determination in skewed populations - Akeem O. Kareem; Isaac O. Oshungade; Gafar M. Oyeyemi; Adebowale O. Adejumo (CBN Journal of Applied Statistics, 2015)
Moving Average Stratification (MAS) is a new competing and simple algorithm for strata boundary determination in Stratified Sampling. It eliminates arbitrary choice of class interval associated with cumulative square root of frequency method (Dalenius and Hodges Rule (DHR) 1959) and the inherent geometric gaps created within strata by Geometric Stratification (GMS) of Gunning & Horgan (2004). It competes favorably well with DHR and GMS in terms of its precision, simplicity and speeds and therefore recommended for use in strata boundaries determination especially in skewed populations.
Keywords: C22; C42; C83.; 330; Class intervals; Homogeneity; Geometric gaps; Stratification; Efficiency